Security in Rights as a Variety of National Security - Valeeva, Guzel Anvarovna; Lipinsky, Dmitry Anatolyevich; Golubcov, Valerii Gennadievich (Cuestiones Políticas, 2020)
Study purpose is to determine the signs of legal security on the basis of existing scientific views and current legislation, excluding its overly broad understanding, leading to the fact that any legal requirement is included in the content of national security. Methodology: the basis is the dialectical method of cognition of the facts of social reality, on which the formal legal and comparative legal approaches are largely based. The methods of analysis and synthesis, abstraction, deduction and induction have found their application both individually and as part of other methods. Main content. We analyzed the features of legal security: normative; legal system stability; focus on eliminating legal threats and others, as well as criticized the widespread understanding of legal security as a form of national security. Conclusions. It is proved that it is necessary to distinguish between such phenomena as legal security and legal security as a form of national security, while the latter is part of legal security. In general, the entire block of legal security is not included in the content of national security.